Juvenile pathogen exposure affects the presence of personality in adult field crickets - DiRienzo, Nicholas; Niemelä, Petri T.; Skog, Anu; Vainikka, Anssi; Kortet, Raine (Frontiers in Ecology and Evolution, 2015)
Despite the ever increasing interest in animal personalities, i.e. among-individual variation in behavior, there are still several gaps in our understanding of how experiences during ontogeny influence the expression of behavior in adulthood. Immune challenges during ontogeny have been proposed to drive feedback loops between investment in immune function and personality type. In this study we investigate the effects of an early immune challenge, in the form of an introduced bacterial pathogen, on the development of personality in field crickets. Our results indicate that early pathogen exposure does not influence life history characteristics, immune response, or mean level of boldness behavior. Instead, early immune challenge affects the presence of personality later in the adult stage. Specifically, immune challenged individuals lack repeatability in some aspects of boldness behavior, indicating that among-individual variation is not present, while non-immune challenged individuals remain repeatable in their boldness behavior. This study joins a slowly growing body of literature indicating that experiences during ontogeny can have large influences on the among-individual differences in behaviors, thus affecting the presence of personality as adults.